1995
DOI: 10.1093/infdis/171.6.1411
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Human Immunodeficiency Virus Type 1 RNA Load and Appearance of Drug-Resistant Virus Populations in Persons Treated with Lamivudine (3TC)

Abstract: The effect of the appearance of drug-resistant human immunodeficiency virus type 1 (HIV-1) on viral RNA load was studied in patients treated with the reverse transcriptase inhibitor lamivudine. During the first 12 weeks of treatment, HIV-1 RNA concentrations and amino acid changes in codon 184, causing high-level resistance to lamivudine, were determined in longitudinal serum samples from HIV-1 p24 antigen-positive and -negative patients. A marked decline in the amount of HIV-1 RNA (approximately 95% below bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
324
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(351 citation statements)
references
References 21 publications
22
324
1
4
Order By: Relevance
“…Mutations in the YMDD motif of the HBV polymerase gene, potentially associated with diminished response to lamivudine, [6][7][8][9] were detected as described. 5,10 During the course of the study, we used an operational definition of virological breakthrough (HBV DNA Ͼ10 pg/mL on 2 successive determinations, after at least 2 previous values had been undetectable) to identify patients for whom YMDD-mutant HBV evaluation would be appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in the YMDD motif of the HBV polymerase gene, potentially associated with diminished response to lamivudine, [6][7][8][9] were detected as described. 5,10 During the course of the study, we used an operational definition of virological breakthrough (HBV DNA Ͼ10 pg/mL on 2 successive determinations, after at least 2 previous values had been undetectable) to identify patients for whom YMDD-mutant HBV evaluation would be appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, mutations at codons 41, 67, 70, 210, 215, and 219 of reverse transcriptase (RT) typically confer resistance to zidovudine (ZDV) (6,12,13,27). Similarly, mutation M184V in RT has been shown to be specifically associated with high-level (Ն50-fold) phenotypic resistance to lamivudine (3TC) (1,22,28). No "specific" mutation(s) associated with moderate levels of phenotypic resistance (4-to Ͻ50-fold) to 3TC has been described before.…”
mentioning
confidence: 99%
“…The replication fitness deficit conferred by the M184V mutation in reverse transcriptase, which causes highlevel resistance to the cytosine analogs lamivudine and emtricitabine, has been the subject of extensive study (reviewed in reference 132). M184V occurs frequently in viral isolates from patients failing lamivudine or emtricitabine therapy (63,153). M184V has a fitness similar to that of the wild type in most T-cell lines where nucleotide concentrations are high (10) but reduced fitness in primary cells that have limited nucleotide pools, such as PBMCs and macrophages (3,10,129).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%
“…Early observations of viral load rebound during lamivudine monotherapy and lamivudine-containing regimens demonstrated that plasma HIV-1 RNA concentrations remained lower than pretherapy levels despite the uniform presence of M184V in plasma viruses (132,153). However, other studies have shown that lamivudine does exert some antiretroviral effect on the M184V mutant, suggesting that the incomplete viral rebounds that occur may represent residual antiviral activity rather than selection for a mutant with reduced fitness (139).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%